Menyelamatkan Anak dari Stunting dengan Pemberdayaan Keluarga Komprehensif - Listia Dwi Febriati; Muflih Muflih; Tri Mei Khasana; Rahayu Widaryanti; Vivien Lin; Carolina Alya (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The prevalence of stunting cases has begun to decline, but there is an increase in cases of underweight and wasting, if this is not handled properly it will add to new stunting cases. Comprehensive family empowerment is one approach that can be used to overcome this problem. The method used in this activity includes education regarding providing complementary foods with breast milk (MP-ASI). This activity will be held in July 2024 with 29 mothers participating who have underweight and wasting toddlers. Most mothers do not know whether their children's nutritional status is in the underweight or wasting category. Apart from that, most mothers complain that their children have difficulty eating, are picky about food and do not consume a variety of foods, including animal protein. After participating in the activity, mothers understand more about their child's nutritional status and know the appropriate and responsive practices for providing complementary feeding.